The Role of Spatial Patterns of Low Impact Development in Urban Runoff Pollution Control Within Parcel Based Catchments - Ma, Yukun; Zhao, Hongtao (Frontiers in Environmental Science, 2022)
Landscape patterns significantly affect urban runoff pollution, and a reasonable arrangement of pervious patches in urban catchments is critical to control urban non-point-source pollution. Low impact development (LID) can be recognized as a pervious surface type, and many previous studies have analyzed the LID performance at a system scale. However, the influence of the LID spatial distribution on runoff pollutant transport at a catchment scale remains unclear. This study analyzed the influence of pervious/impervious patterns on runoff pollution within two urban catchments constructed with LID. It was found that the runoff pollution was influenced by the area ratio, circumference, shape, and pervious patch connectivity of pervious surfaces (i.e., LID). Catchments with high perviousness ratios are more efficient in reducing the runoff volume and suspended solids, and LID should focus on removing runoff pollutants at catchments with high imperviousness ratios. Six typical landscape metrics that represented the fragmentation, complexity and vergence of pervious surfaces were selected to investigate the influence of pervious/impervious patterns on runoff pollution. The results show that larger fragmentation, smaller complexity and smaller vergence of pervious patches result in larger runoff volumes and more pollutants. Therefore, it is recommended that large pervious areas should be retained and close to one another to enhance the retention capacity of LID, and the outline of pervious patches should be long and irregular to reduce pollution confluence. The results of this study are helpful in arranging LID structures for efficient runoff regulation and pollution control at an urban catchment scale.